So ist Lernen klasse der beste Lernweg für mein Kind - Endres, Wolfgang 1946-; Bernard, Elisabeth 1950- (Kösel, 1992)
SCHLAGWÖRTER<S>: Lerntyp<S>. Motivation<S>. Konzentration<S>. Selbständigkeit<S>. Lernmethoden<S>. Prüfung<S>
Keywords: Lernen; Schuljahr 3-8; Kind; Schulkind; Lerntechnik; Ratgeber